Penerapan Metode Pasteurisasi untuk Meningkatkan Daya Simpan dan Mutu Minuman Khas Sinjai (Minas) - Irdan Syam; Ratnawaty Fadilah; Andi Sukainah (Jurnal Pendidikan Teknologi Pertanian, 2023)
Minas is a typical drink with the main ingredient of cassava tape which comes from Sinjai Regency, South Sulawesi. This study aims to determine the effect of pasteurization and storage temperature on the shelf life and quality of typical Sinjai (Minas) drinks. This research is a quantitative research (experiment) using a Completely Randomized Design (CRD) factorial pattern consisting of 4 treatments with 3 repetitions, namely: P1T1 (Minas without pasteurization with room temperature storage), P1T2 (Minas without pasteurization with refrigerator temperature storage) , P2T1 (Minas pasteurization with storage at room temperature), P2T2 (Minas pasteurization with storage at refrigerator temperature). The data obtained will be analyzed with analysis of variance and advanced test DMRT (Duncan Multiple Range Test) which is processed using SPSS version 22. The results showed that pasteurization and storage temperature have an influence on the shelf life and quality of Minas. The best treatment based on the DMRT test is P2T2 treatment (Minas pasteurization with refrigerator temperature storage) with TAT on the 10th day of 0.64%, pH on the 10th day of 3.84, and ALT on the 10th day of 3, 13 log cfu / ml.Penelitian ini bertujuan mengetahui pengaruh pasteurisasi dan suhu penyimpanan terhadap daya simpan dan mutu minuman khas Sinjai (Minas). Penelitian ini merupakan penelitian kuantitatif (eksperimen) dengan menggunakan rancangan percobaan Rancangan Acak Lengkap (RAL) pola faktorial yang terdiri atas 4 perlakuan dengan 3 kali pengulangan yaitu: Minas tanpa pasteurisasi (kontrol), Minas yang dipasteurisasi dengan suhu 77 0C selama 15 menit dan penyimpanan pada suhu ruang dan suhu dingin (refrigerator) dengan parameter pengamatan Angka Kapang/Khamir (AKK), Total Mikroba/TPC (Total Plate Count), pH (Potensial Hydrogen), Total Asam Tertitrasi (TAT) dan hedonik. Data yang diperoleh akan dianalisis dengan analisis sidik ragam dan uji lanjut DMRT (Duncan Multiple Rate). Hasil penelitian menunjukkan bahwa perlakuan pasteurisasi pada penyimpanan suhu dingin (refrigerator) merupakan perlakuan terbaik untuk meningkatkan daya simpan dan mutu minuman khas Sinjai (Minas).